Implementation of a Donor Milk Program Is Associated with Greater Consumption of Mothers' Own Milk among VLBW Infants in a US, Level 3 NICU. (May 2016) - Parker, Margaret G.K.; Burnham, Laura; Mao, Wenyang; Philipp, Barbara L.; Merewood, Anne
Background: It is unclear whether use of donor milk (DM) changes the provision of mothers' own milk (MOM) to very low birth weight (VLBW) infants in the neonatal intensive care unit (NICU). Objectives: To determine whether (1) the rates of any MOM and human milk consumption at feeding initiation and discharge and (2) the proportion of VLBW infants who stopped consuming any MOM and human milk during hospitalization changed in the 2 years after versus before implementation of a DM program in a US, inner-city, level 3 NICU. Methods: We studied VLBW infants admitted to Boston Medical Center in the 2 years before (n = 74) and after (n = 80) implementation of a DM program (June 2011). We used multivariable logistic regression to compare milk consumption at feeding initiation and discharge and Cox proportional hazards to compare the proportion of infants that stopped consuming milk during the hospitalization pre and post our DM program. Results: After adjustment for maternal race, age, insurance, delivery type, gestational age, and birth weight, we found a 6.0-fold increased odds (95% CI, 2.0-17.7) of consuming MOM at discharge and a 49% reduction in the cessation of MOM consumption during hospitalization (hazard ratio [HR], 0.51; 95% CI, 0.28-0.93) in the 2 years after versus before our DM program. Conclusion: Implementation of a DM program was associated with greater consumption of MOM throughout hospitalization and at discharge among VLBW infants. Implementation of DM programs may augment support of mothers to provide breast milk in level 3 NICUs.